Effects of 15-Year-Old Plantation on Soil Conditions, Spontaneous Vegetation, and the Trace Metal Content in Wood Products at Kipushi Tailings Dam - Mwanasomwe, Jacques Kilela; Langunu, Serge; Shutcha, Mylor Ngoy; Colinet, Gilles (Frontiers in Soil Science (Online), 2022)
Phytostabilization is a more appropriate way for rehabilitation of metal-polluted environments in the Copperbelt region. A 1.5-hectare tree planting trial had been installed on the tailings dam (TD) with the help of organic matter (OM) mixed to topsoil. Then, 15 years later, this study aimed to evaluate the performance of the tree plantation, in regard to soils and spontaneous vegetation. The Cu and Co concentration was higher in the reclaimed soil compared with the unreclaimed. Acacia auriculiformis , Acacia polyacantha , Albizia lebbeck , Pinus sylvestris , Psidium guajava , Senna siamea , Senna spectabilis , and Syzygium guineense responded well to the criteria of phytostabilization, whereas Leucaena leucocephala was very invasive. Metal concentration was manifold higher in charcoals than in woods (Zn: 3.8–39.8 mg kg −1 in wood versus 272–523 mg kg −1 in charcoal) with no differences between charcoals regardless of the origin. The tree implantation aided with amendments can meet the criteria of phytostabilization through good survival and regeneration in the heavily contaminated TD.